THE IMPACT OF PRODUCT QUALITY, BRAND IMAGE, AND PRICE PERCEPTION ON BOTTLED MINERAL WATER (BMW) PURCHASING DECISION IN JABODETABEK - Herry Sussanto; Muhammad Rafli Alfarizi (International Journal Multidisciplinary Science, 2023)
The aims of the research are to find out and to analyze the impact of Product Quality, Brand Image, and Price Perception partially and simultaneously to the purchasing decision of Aqua, the brand of bottled mineral water. Primary data is used as the method of analyzing. The testing phases are done by using validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient determination test. The data is taken by using questionnaire, and the valid data gained in this research is 100 respondents who are the consumers of Aqua. The method of sampling used in this research is non probability sampling with accidental sampling technique. The instrument used in conducting the tests is SPSS 25 version The results showed that the variables of Product Quality, Brand Image, and Price Perception had a simultaneous and partial impact on the purchasing decision of bottled mineral water, Aqua. And the variable that has dominant impact on the purchasing decision of bottled mineral water, Aqua, is the Product Quality variable.